2018
DOI: 10.3390/medicines5030105
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging and Chronic Osteoarthritis

Abstract: Background: Aging is commonly accepted as a time period of declining heath in most cases. This review aimed to examine the research base concerning the use of the term ‘successful aging’, a process and outcome deemed desirable, but challenging to attain. A second was to provide related information to demonstrate how health professionals as well as individuals can aim for a ‘successful aging’ process and outcome, despite the presence of disabling osteoarthritis. Methods: Information specifically focusing on ‘su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Helme (2001) reported that elderly individuals with chronic disease who were capable of good pain management and with highly empathetic attitudes also aged more successfully [33]. At the same time, individuals with chronic diseases have been reported to behave in a more controlled manner than those without such diseases, while successful aging is accompanied by good pain management and the overcoming of physical limitations [34,35]. We think that our finding shows that individuals with chronic diseases in this study had good pain management.…”
Section: Discussionsupporting
confidence: 53%
“…Helme (2001) reported that elderly individuals with chronic disease who were capable of good pain management and with highly empathetic attitudes also aged more successfully [33]. At the same time, individuals with chronic diseases have been reported to behave in a more controlled manner than those without such diseases, while successful aging is accompanied by good pain management and the overcoming of physical limitations [34,35]. We think that our finding shows that individuals with chronic diseases in this study had good pain management.…”
Section: Discussionsupporting
confidence: 53%
“…Osteoarthritis (OA) is a joint disease, affecting the middle-aged to elderly [ 99 ]. An ethanol extract of SCE was shown to exert a protective effect against cartilage degradation in a monosodium iodoacetate (MIA)-induced OA rat model [ 100 ].…”
Section: Health Promoting Effects Of Sce Constituentsmentioning
confidence: 99%